16.7k views
3 votes
What is the solution to this equation 10x - 3(x-6)- x + 30

A. x=6
B. x= 2
C. x = 4
D. x=8

User Bebbi
by
5.6k points

2 Answers

3 votes

Explanation:

x=2

User Rtcoms
by
5.3k points
4 votes

Answer:

option B)

x = 2

Explanation:

Given in the question the equation:

10x - 3(x- 6) = x + 30

Simplify the left side

10x - 3(x - 6) = x + 30

10x - 3x + 18 = x + 30

rearrange the terms and containing x to the left side of the equation and add accordingly

x(10 - 3 - 1) = (30 - 18)

x(10 - 4) = (12)

x(6) = 12

6x = 12

Divide each term by 6 and simplify

x = 12/6

x = 2

User Arets Paeglis
by
6.3k points